Praxagoras of Cos on arteries, pulse and pneuma : fragments and interpretation - Lewis, Orly. (Studies in Ancient Medicine, 2017)
The distinction that Praxagoras of Cos (4th-3rd c. BC) made between arteries and veins and his views on pulsation and pneuma are two significant turning points in the history of ideas and medicine. In this book Orly Lewis presents the fragmentary evidence for this topic and offers a fresh analysis of Praxagoras' views on the soul and the functions of the heart and pneuma. In so doing, she highlights the empirical basis of Praxagoras' views and his engagement with earlier medical debates and with Aristotle's physiology. The study consists of an edition and translation of the relevant fragments (some absent from the standard 1958 edition) followed by a commentary and a synthetic analysis of Praxagoras' views and their place in the history of medicine and ideas.